2023
DOI: 10.3934/jimo.2022012
|View full text |Cite
|
Sign up to set email alerts
|

A game theoretic strategic model for understanding the online-offline competition and fairness concern under community group buying

Abstract: <p style='text-indent:20px;'>The continuous growth of e-commerce leads to the emergence of a new supply chain model known as community group buying, which is advantageous to address the inefficiencies and higher costs of intermediate processes. However, its appearance results in fairness concerns for other participating merchants. In this regard, we construct a model with two suppliers, one wholesaler, and two retailers for three different scenarios of the initial status, fairness neutrality, and fairnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…In a supply chain setting, Tran and Desiraju (2016) analyzes the value of group purchasing provided by retailers to manufacturers and indicates that profit margins are significantly affected by market heterogeneity. Wang and Song (2023) investigate the group-buying activity and conclude that the online retailer is beneficial for social welfare which is impacted by investment conversion efficiency. Chen et al (2022) focus on information intensity that may contribute to the rush behavior of group buying.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a supply chain setting, Tran and Desiraju (2016) analyzes the value of group purchasing provided by retailers to manufacturers and indicates that profit margins are significantly affected by market heterogeneity. Wang and Song (2023) investigate the group-buying activity and conclude that the online retailer is beneficial for social welfare which is impacted by investment conversion efficiency. Chen et al (2022) focus on information intensity that may contribute to the rush behavior of group buying.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of fairness concerns, the emergence of community group buying has raised fairness concerns among other participating merchants. Wang and Song [14] thus construct a game model under three different scenarios, namely, initial state, fairness-neutral, and fairness-concerned, and the study shows that fairness-concerned has a very limited impact on the social welfare, affecting only the internal distribution of benefits.…”
Section: Development Trends Of Community Group Buyingmentioning
confidence: 99%
“…To ensure the quality of fresh food and the profitability of merchants in community group buying, Shui and Li [16] designed a community group buying pricing model and a cold chain vehicle route planning model. Wang and Song [17] found that the emergence of community group buying caused concern about the fairness of businesses. They also found that online retailers would weaken the market position of offline sellers after entering the market.…”
Section: Online Group Buying Pricing Strategiesmentioning
confidence: 99%